Cardiac Arrhythmias Mechanisms, Pathophysiology, and Treatment - Aronow, Wilbert S. (IntechOpen, 2014)
This book is useful for physicians taking care of patients with cardiac arrhythmias and includes six chapters written by experts in their field. Chapter 1 discusses basic mechanisms of cardiac arrhythmias. Chapter 2 discusses the chronobiological aspects of the impact of apnoic episodes on ventricular arrhythmias. Chapter 3 discusses navigation, detection, and tracking during cardiac ablation interventions. Chapter 4 discusses epidemiology and pathophysiology of ventricular arrhythmias in several noncardiac diseases, methods used to assess arrhythmia risk, and their association with long-term outcomes. Chapter 5 discusses the treatment of ventricular arrhythmias including indications for implantation of an AICD for primary and for secondary prevention in patients with and without congestive heart failure. Chapter 6 discusses surgical management of atrial fibrillation.